Effects of coumarin substituents on the photophysical properties of newly synthesised phthalocyanine derivatives - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2009)
In this study, synthesis of new ligands, 8-hydroxy-3-[p-(3',4'-dicyanophenoxy)-phenyl]coumarin and 8-hexyloxy-3-[p-(3',4'-dicyanophenoxy)-phenyl]coumarin, and their phthalocyanines, 2,9,16,23-tetrakis[8-hexyloxy-3-(4-oxyphenyl)coumarin]-metal-free and metallophthalocyanines {M[Pc(OBzCou)4] (M=2H, Zn(II), Co(II); Bz: benzene; Cou: coumarin)} were synthesised. The novel chromogenic compounds were characterised by elemental analysis: 1H NMR, 13C NMR, MALDI-TOF, IR and UV-vis spectral data. The effect of coumarin substituents on the photophysical properties of metal-free (H2Pc) and zinc phthalocyanines (ZnPc) derivatives has been examined. Spectrophotometric measurements revealed that coumarin-substituted ZnPc derivatives were in the unaggregated form, whereas those of H2Pc species were in aggregated form. It means that substitution of coumarin derivative prevents the cluster formation in the presence of zinc ion in the centre of Pc.
Keywords: phthalocyanines; fluorescence; coumarin derivatives; aggregation; cobalt; zinc; RECEPTOR FUNCTIONAL PHTHALOCYANINES; METAL-ION BINDING; DENDRITIC PHTHALOCYANINES; AGGREGATION BEHAVIOR; ELECTROCHEMISTRY; COMPLEXES; FLUORESCENCE; SPECTROSCOPY; MOIETIES; LIGAND